The role of corporate social responsibility in social development projects: A case of multinational telecommunication companies in Dar es Salaam - Justine, Fortunata (Mzumbe University, 2024)
Dissertation submitted in partial fulfillment of the requirements for award of the degree of Master of Business Administration in Corporate Management (MBA-CM) of Mzumbe University